Genome-wide identification and expression analysis of sulphate transporter (SULTR) genes under sulfur deficiency in Brachypodium distachyon - Tombuloglu, Huseyin; Filiz, Ertugrul; Aydin, Mehtap; Koc, Ibrahim (Springer India, 2017)
Sulphur is an important mineral element for plant growth and development. It involves in a number of metabolic processes with crucial functions. This study has performed a genome-wide analysis of sulfate transporter (SULTR) genes in Brachypodium distachyon. Ten putative SULTR genes were identified in Brachypodium genome. BdSULTR genes included 6-17 exons encoding a protein of 647-693 residues with basic nature. BdSULTR proteins included both sulfate_transp (PF00916) and STAS (PF01740) domains. BdSULTRs were classified into 4 groups based on the phylogenetic distribution. Promoter regions of all BdSULTR genes, except for BdSULTR3;3 and 3;5 included the SURECOREATSULTR11 elements. A considerable structural overlap was identified between superimposed SULTR1;3 and 3;1 proteins, indicating that SULTR1 members may also involve in plant stress response/tolerance like SULTR3 members. Microarray and RNA-Seq analyses also revealed the differential expression of SULTR 1 and 3 genes under different biotic/abiotic stresses. Protein-protein interaction partners of BdSULTRs were mainly related with adenylyl-sulfate kinases, 5'-adenylylsulfate reductases, ATP sulfurylases, and acyl carrier proteins. Moreover, expression profiles of identified BdSULTR genes under S-deficiency were analyzed using RT-qPCR. It was revealed that BdSULTR1;1 and 3;1 are highly expressed in plant roots as similar to tenfold and similar to fivefold, respectively, while BdSULTR2 (similar to 15-fold) and 3;1 (similar to twofold) are abundantly expressed in leaf tissues.
Keywords: Abiotic stress; Microarray; Protein interactions; SULTR; Sulphur deficiency; SURE box